(untitled) (Global Journal of Human-Social Science, 2020)
The overall objective of this study is to assess the effects of institutional factors on the attractiveness of foreign direct investment (FDI) in sub-Saharan African economies (SSA). To achieve this goal, we use five (05) institutional quality indicators. A dynamic model in panel data is specified and estimates are made by the System of Generalized Moments (MMG) method in the period 2007-2017. The main results obtained show that: (i) the quality of certain institutions (the quality of country policies, the quality of regulation and the rule of law) conditions the level of deepening of the FD and its capacity to make a significant contribution to growth; (ii) We also show that the low quality of regulation and the rule of low as well the uncertainty linked to the political stability of some countries of SSA hinder the entry of FDI in this region; (iii) To contribute to the emergence of more productive and attractive economic systems, the study supports the idea of promoting a legal and regulatory framework providing more guarantees, democracy and restoring political stability.